2000
DOI: 10.1111/j.1471-0528.2000.tb11653.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparison and economic evaluation of laparoscopic‐assisted hysterectomy and abdominal hysterectomy

Abstract: Objectives To determine the safety, cost effectiveness and effect on quality of life of laparoscopicassisted vaginal hysterectomy (LAVH) compared with total abdominal hysterectomy (TAH) in the management of benign gynaecological disease.Design Randomised controlled trial and economic evaluation.Setting Three hospitals in the West of Scotland.Participants Two hundred women scheduled for an abdominal hysterectomy for benign gynaecological disease.Main outcome measures Conversion rate of LAVH to TAH, complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 25 publications
7
71
2
2
Order By: Relevance
“…TCRE or ablation is an effective and possibly cheaper alternative to hysterectomy with faster recovery although re-treatment is sometimes needed [75]. The CREST study on the complication rate for minor and major operations, reports a 25% complication rate for vaginal hysterectomy and a 43% for abdominal hysterectomy [76]. The VALUE study confirmed that more than 10% of women treated by hysterectomy for DUB reported immediate or long-term complications [77].…”
Section: Hysterectomysupporting
confidence: 66%
“…TCRE or ablation is an effective and possibly cheaper alternative to hysterectomy with faster recovery although re-treatment is sometimes needed [75]. The CREST study on the complication rate for minor and major operations, reports a 25% complication rate for vaginal hysterectomy and a 43% for abdominal hysterectomy [76]. The VALUE study confirmed that more than 10% of women treated by hysterectomy for DUB reported immediate or long-term complications [77].…”
Section: Hysterectomysupporting
confidence: 66%
“…At the end of follow-up, 12 weeks after surgery, there were no significant differences between the two patient groups. Lumsden et al [74] used the Euroqol Health Questionnaire (Euroqol HQ [34]) for 166 hysterectomy patients (1b). The groups were compared 1, 6, and 12 months after surgery, but there were no significant differences in QoL.…”
Section: Hysterectomymentioning
confidence: 99%
“…In the trial by Lumsden et al [23], 76 of the 95 patients in the LH arm had the "uterine arteries divided using the Endo GIA disposable stapling device" and yet the Review [20] classified the LHs in this trial as "non-categorisable". The Review [20] makes important errors with regard to ureteric injuries in this trial by quoting two ureteric injuries in the LH arm and one in the AH arm (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The recent Cochrane Review [20] on the different surgical approaches to hysterectomy for benign gynaecological diseases compares ureteric injuries from LH and AH, with the Review citing four published trials [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%